Pengaruh Kualitas Produk, Brand Image Dan Persepsi Harga Terhadap Keputusan Pembelian Laptop Merek Hp (Hewlett Packard) Pada Mahasiswa Di Kota Surabaya - Adinda Nila Puspita Sari; Ugy Soebiantoro (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
This study aims to analyze the effect of product quality, brand image, and price perception on the purchasing decisions of HP (Hewlett-Packard) laptop products among university students in Surabaya. This research employs a quantitative approach with a sample of 112 respondents selected using purposive sampling, with the criteria being students who have previously purchased and used HP laptops. The data analysis technique applied in this study is Structural Equation Modeling based on Partial Least Squares (SEM-PLS), which includes validity testing, reliability testing, and hypothesis testing. The results indicate that product quality does not have a significant effect on purchasing decisions. In contrast, brand image has a positive and significant influence on purchasing decisions, suggesting that a strong brand image can enhance consumer trust. Additionally, price perception also has a positive and significant effect on purchasing decisions, indicating that the alignment between price and perceived benefits is an important factor influencing consumers. This study concludes that brand image and price perception are the main factors affecting the purchasing decisions of HP laptops among university students in Surabaya.